Corporate Social Responsibility PT. Perkebunan Nusantara VIII, Case Study: Partnership Program in PKBL - Priya, Evan Husada; Rudito, Bambang (Journal of Business and Management, 2013)
Indonesia is one of the largest countries in South East Asia both in terms of population density and the width of territory.Â Unfortunately, the entrepreneurial percentage in this country represents only 1,56% of the total population while the ideal number of the entrepreneurial percentage is 2% or more. Indonesia is now ranked 115 in the world and 23 out of 41 countries in the Asia-Pacific region from the level of economy and entrepreneurial. PKBL is the BUMN Partnership Program that aims at empowering the society through the use of funds from the profits of BUMN that is set aside with the approval of the General Meeting of Shareholders of the BUMN. Total provision for income program funding is in the maximum of 2% (two percent) of the net profit for the Partnership Program (Program Kemitraan) and a maximum of 2% (two percent) of the net profit for the Community Development Program (Bina Lingkungan). PKBL is expected will increase the entrepreneur rate and also decrease the number of unemployment and poverty with its Partnership Program. The fund will use to help UKM to develop their business and became sustain. Because UKM in Indonesia has grown more and more, and has created a huge impact as a business unit in Indonesia as a business unit that has proportion about 98 percent of the total units in Indonesia and have absorbed approximately 88.6 million workers. The Purpose of this final project is to achieve evaluations for community development program of PT. Perkebunan Nusantara VIII which is Partnership program. This project purpose is to analyze the effectiveness of the program. The results of the program will also be analyzed to discover whether it is already accomplish its target or not. Â Keyword: entrepreneur, corporate social responsibilities, small and medium enterprise